Persepsi Peserta Didik terhadap Metode Blended Learning dengan Google Classroom - Sugama Maskar; Endah Wulantina (Jurnal Inovasi Matematika, 2019)
The Industrial Revolution 4.0 encourages change in the process of education and online learning is one of the challenges that must be faced. Blended Learning is one solution to that change. The purpose of this study was to find out the attitudes of students towards the learning process through Blended Learning with a sample of Statistics classes atUniversitas Teknokrat Indonesia. The online learning process is done using Google Classroom. Data collection and analysis techniques use attitude scale questionnaires consisting of two variables, attitudes toward the learning process and attitudes towards material understanding, which are supported by 9 indicators and 21 statements. The results of this study indicate that students feel the learning process with the Blended Learning Method through Google Classroom makes the learning process interesting, effective, fosters motivation, fosters an attitude of independent learning, active, and creative. In addition, this method can also improve students' understanding and learning outcomes. However, students feel the learning process is inefficient because it requires them to have a data package. Therefore, the role of the government is very important, such as facilities and infrastructure to support the Blended Learning process so that students can stay connected to the free internet.